2000
DOI: 10.1046/j.1365-2044.2000.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of cisatracurium 0.15 mg.kg−1 during nitrous oxide–opioid anaesthesia in infants and children

Abstract: SummaryWe studied the neuromuscular and cardiovascular effects of a single, rapidly administered intravenous dose of cisatracurium 0.15 mg.kg 21 in 27 infants (aged 1±23 months) and 24 children (aged 2± 12.5 years). After midazolam premedication, anaesthesia was induced and maintained with thiopental and alfentanil in addition to nitrous oxide in oxygen. Neuromuscular function was monitored by evoked adductor pollicis electromyography. At least 15 min after intubation, each patient received cisatracurium 0.15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
(29 reference statements)
2
13
0
4
Order By: Relevance
“…19 Similar findings were also observed by Taivainen T et al, Shahram A et al 12,16 These observations of hemodynamic effects of cisatracurium correlates with the observations of our study where group B ( 0.2 mg/kg=4×ED95) found to be hemodynamically more stable than group A (0.15 mg/kg=3×ED95).…”
Section: Hemodynamic Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…19 Similar findings were also observed by Taivainen T et al, Shahram A et al 12,16 These observations of hemodynamic effects of cisatracurium correlates with the observations of our study where group B ( 0.2 mg/kg=4×ED95) found to be hemodynamically more stable than group A (0.15 mg/kg=3×ED95).…”
Section: Hemodynamic Variablessupporting
confidence: 89%
“…Taivainen T et al studied safety and efficacy of cisatracurium 0.15 mg/kg during nitrous oxide opioid anaesthesia in infants and children, found that onset of action was more rapid in infants than children and mean clinical duration of action of cisatracurium 0.15 mg/kg loading dose in infants was 43.3±6 minutes while in children was 36.0±5.4 minutes with p value<0.0001. 16 Sarooshian SS et al also found that young patients have more rapid onset of block than elderly patients because of slow biophase equilibration in elderly patients but clinical duration of action i.e. recovery profile was found to be similar between two groups.…”
Section: Hemodynamic Variablesmentioning
confidence: 96%
“…Muskelrelaxanzien · Cisatracurium · Elektromyographie · Kinderanästhesie · Pharmakodynamik ten Muskelrelaxanzien wie Atracurium [2] und Cisatracurium [18] beobachtet.…”
Section: Schlüsselwörterunclassified
“…Bisher liegen nur wenige Daten zu Wirkung von Cisatracurium im Säug-lingsalter vor [3,15,18].Ziel der vorliegenden Untersuchung war es deshalb den Verlauf der neuromuskulären Blockade nach 0,1 mg/kg Cisatracurium unter Inhalationsanästhesie mit Sevofluran bei Säuglingen und Kindern zwischen 2 und 9 Jahren zu vergleichen.…”
Section: Schlüsselwörterunclassified
See 1 more Smart Citation